Implications of 9/11 Attacks in Waldman’s The Submission - Adhikari, Rashmi Thapa (Patan Prospective Journal, 2023)
This paper scrutinizes the impacts of 9/11 attacks as portrayed in Amy Waldman’s The Submission that is written in 2011 after a decade of the incident. The research shows that the incident of 9/11 opens up both new challenges and opportunities for the people of the world in general and the Americans in particular. The article explains the reasons for the adversities that minorities and women experience in the aftermath of the attacks as depicted in the novel. As the terrorists are men, the incident of 9/11 is generally seen as a masculine event that overshadows the sufferings experienced by the women characters. The objective of the paper is to explore the repercussions of the attacks in the lives of the women as portrayed in the text. The article pictures the trials and tribulations of women from ethnic minorities of the non-western countries. The paper employs the feminist perspective to analyze the traumatic sufferings of the Asian women. I use the concept of E. Kaplan to analyze the fictional data to investigate into the status of ethnic minorities especially women in the post-9/11 situation in the United States of America. The finding of the research implies that women face more identity crisis than their counterparts in the aftermath of the incident regarding life, liberty and pursuit of happiness which are needed to lead lives with dignity.